(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2016)
In recent years, there is a significant decline of cocoa beans in terms of exports value and share after 2010. Several studies claimed that this downward trend was caused by the introduction of an export tax on cocoa beans in 2010. Nevertheless, there are limited studies on the impacts of decreasing cocoa beans exports to the Indonesian economy. Therefore, this study aimed to simulate the impacts of the imposition of export tax on cocoa beans to the economy as well as unemployment. Methodology of this study utilised the Input-Output Table. In particular, this study calculated the impacts of export tax on cocoa beans to the changes of output, primary inputs, and unemployment in several scenarios. The main result of this study was that at extreme scenario, where the cocoa beans sector’s export was eliminated, the impacts on the whole economy and unemployment were insignificant. Moreover, this study found that the impacts on value added such as decreasing of profit were relatively higher than decreasing ra te on the output and others value added such as salary and wages and indirect taxes. On the other hand, this study argued that even though the introduction of export tax effectively reduced raw cocoa beans exports, there was an increasing on the exports’ value on the down stream industries.